Strategic Analysis of Research-Based Learning Management Strategies to Enhance Teacher Competence in Schools - Siminto; Qodir, Abdul (PT. LITERASI SAINS NUSANTARA, 2024)
Amidst the ever-evolving wave of technology and the complexity of student needs, teachers must be equipped with relevant skills and knowledge to provide effective learning experiences. Learning management plays a central role in upholding the quality of education in schools, and the use of appropriate strategies is crucial in this context. This research aims to analyze research-based learning management strategies to enhance teacher competence in schools. The research method employed is a qualitative literature review aimed at community service, particularly in the context of its relevance to teacher competence in schools. Data used were obtained from Google Scholar searches spanning from 2008 to 2023. The study findings indicate that by enhancing teacher competence through the application of research-based learning management strategies, schools can create an environment conducive to the sustainable professional development of teachers. This approach combines management principles with research methods to identify needs, design appropriate training programs, and continuously evaluate their effectiveness. Despite its significant potential, challenges such as resource limitations and contextual factors need to be addressed for successful implementation.